2009
DOI: 10.1542/peds.2009-0783
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Exposure From Parenteral Nutrition in Preterm Infants: Bone Health at 15-Year Follow-up

Abstract: OBJECTIVE: Aluminum has known neurotoxicity and may impair short-term bone health. In a randomized trial, we showed reduced neurodevelopmental scores in preterm infants who were previously exposed to aluminum from parenteral nutrition solutions. Here, in the same cohort, we test the hypothesis that neonatal aluminum exposure also adversely affects long-term bone health, as indicated by reduced bone mass. METHODS: Bone area (BA) and bone mineral content (BMC) of lumbar spine, hip, and whole body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 18 publications
1
65
0
Order By: Relevance
“…However, there are no similar limits of aluminum contamination of small volume components such as calcium gluconate, which accounts for 85% of the aluminum contamination in infant PN therapy. Despite these recommendations, the level of aluminum contamination of infant PN therapy is reported to be 10-60 μg/kg per day [3][4][5][6]. Premature infants with immature kidneys and high aluminum exposure are particularly vulnerable to aluminum toxicity.…”
mentioning
confidence: 99%
“…However, there are no similar limits of aluminum contamination of small volume components such as calcium gluconate, which accounts for 85% of the aluminum contamination in infant PN therapy. Despite these recommendations, the level of aluminum contamination of infant PN therapy is reported to be 10-60 μg/kg per day [3][4][5][6]. Premature infants with immature kidneys and high aluminum exposure are particularly vulnerable to aluminum toxicity.…”
mentioning
confidence: 99%
“…The residual of available aluminum (Al) in biologically ecosystem has been substantially increasing during recent years, so Al contamination becomes an increasing problem in human society (Hewitt et al 1990;Rengel 2004;Fewtrell et al 2009). It was reported that Al exposure caused delayed hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized trial in preterm infants receiving either standard aluminum solutions or specially prepared low-aluminum parenteral nutrition solution, in which calcium gluconate was replaced by calcium chloride, we showed that infants fed the low-aluminum solution had significantly higher scores on the Bayley mental development index at 18 mo corrected age (14). More recently, at age 15 y, we reported higher lumbar spine BMD in these subjects (15). Furthermore, subjects exposed to aluminum concentrations above the median during the neonatal period had a significantly lower hip bone mineral content.…”
Section: Implications For the Nutritional Management Of Preterm Infantsmentioning
confidence: 82%